2019
DOI: 10.1017/s1460396919000955
|View full text |Cite
|
Sign up to set email alerts
|

A review of predictive, prognostic and diagnostic biomarkers for brain tumours: towards personalised and targeted cancer therapy

Abstract: Background: Brain tumours are relatively rare disease but present a large medical challenge as there is currently no method for early detection of the tumour and are typically not diagnosed until patients have progressed to symptomatic stage which significantly decreases chances of survival and also minimises treatment efficacy. However, if brain cancers can be diagnosed at early stages and also if clinicians have the potential to prospectively identify patients likely to respond to specific treatments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…The first attempts to determine tumor ctDNA in the blood of patients with GBM relied on the identification of prognostically significant genetic markers, such as methylation profiles of individual gene promotors, loss of heterozygosity of chromosome 10, IDH1 mutation, and EGFRvIII deletion [59][60][61][62][63][64]. Some studies have shown that tumor ctDNA can be isolated from the GBM patient's blood in 15-88.8 % of cases [54,62,[65][66][67][68][69][70][71].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…The first attempts to determine tumor ctDNA in the blood of patients with GBM relied on the identification of prognostically significant genetic markers, such as methylation profiles of individual gene promotors, loss of heterozygosity of chromosome 10, IDH1 mutation, and EGFRvIII deletion [59][60][61][62][63][64]. Some studies have shown that tumor ctDNA can be isolated from the GBM patient's blood in 15-88.8 % of cases [54,62,[65][66][67][68][69][70][71].…”
Section: Cell-free Dnamentioning
confidence: 99%
“…For this reason, repeated attempts have been made over the last few years to identify specific biomarkers that could be detected/measured using noninvasive methods and that would allow early diagnosis and disease monitoring, including controlling the response to treatment [84].…”
Section: Mirnas and Molecular Chaperones In Brain Tumorsmentioning
confidence: 99%
“…37,38 Cancer biomarkers can be either (1) diagnostic (used to identify whether a patient has a specific disease condition), (2) predictive (used to predict response to specific therapeutic interventions) or (3) prognostic (used to inform physicians regarding the risk of clinical outcomes such as cancer recurrence or disease progression). 34,35,[39][40][41][42] According to Osei et al, 34,35 understanding the molecular mechanisms and signalling pathways of biomarkers can potentially lead to personalised and targeted treatment via therapeutic targeting of specific genetic aberrant pathways which play key roles in malignant tumour formation and may provide optimal treatment choices in clinical practice. Biomarkers commonly used for diagnosis, prognostication and therapeutic monitoring can be obtained through either liquid or tissue biopsies.…”
Section: Liquid Biomarkers For Management Of Paediatric Neuroblastomamentioning
confidence: 99%
“…Copy number alterations (CNAs) are somatic changes to chromosome structure that result in either a gain or loss of copies in sections of the DNA and have been reported to correlate with the development and progression of cancer. 35,83 According to Combaret et al, 83 high copy numbers are strongly associated with rapid tumour progression and poor outcome, independent of tumour stage or patient age and have become an important factor in treatment stratification. Several studies 41,[93][94][95][96][97][98][99][100][101] have measured MYCN copy number in cfDNA of MYCN-amplified neuroblastoma patients using qPCR to investigate whether qPCR is capable of measuring MYCN gene amplification in serum95 and if MYCN amplification status can identify high-risk neuroblastoma patients who may benefit from early therapeutic intervention or correlates with neuroblastoma prognosis and patient survival.…”
Section: Copy Number Alterations (Cnas) In Cfdnamentioning
confidence: 99%
See 1 more Smart Citation